Morphometric changes of the River Bodrog from the late 18th century to 2006 - Mecser, Nikoletta; Demeter, Gábor; Szabó, Gergely (Acta Geographica Debrecina Landscape & Environment series, 2009)
The river regulations of the 19th century have affected each of our rivers to a different degree. In the case of the River Bodrog it was stronger than the average. In our paper a section of the river between Bodroghalász and Szegi was examined, the extent and intensity of river channel changes was intended to be determined. The applied series of maps and aerial photos was georeferred and the river channel was vectorized. The morphometric parameters of the channel were measured and the changes were evaluated using the created database. From methodological aspect we concluded that the 9 variables can be grouped into 3 factors therefore most of the indexes can be substituted. We measured the changes of length and lateral shift of the channel using GIS methods. Three development periods were identified based on our results. In the first period the development of the river was characterized by natural processes. Then, the development of the river altered owing to the antropogenic impacts. In this transient phase the average shifting of the channel was 7.43 m/y. In the third term this value reduces to 0.2 m/y as the river is getting to reach the equilibrium stage.